2016
DOI: 10.1016/j.cplett.2016.10.072
|View full text |Cite
|
Sign up to set email alerts
|

Tautomeric stabilities of 4-fluorohistidine shed new light on mechanistic experiments with labeled ribonuclease A

Abstract: Ribonuclease A is the oldest model for studying enzymatic mechanisms, yet questions remain about proton transfer within the active site. Seminal work by Jackson et al. (Science, 1994) labeled Ribonuclease A with 4-fluorohistidine, concluding that active-site histidines act as general acids and bases. Calculations of 4-fluorohistidine indicate that the π-tautomer is predominant in all simulated environments (by ~17 kJ/mol), strongly suggesting that fluoro-labeled ribonuclease A functions with His119 in π-tautom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…For histidine, the different tautomeric states (τ and π) of 2-fluoro and 4-fluoro histidines and analogues were considered. 195051 The fluorine chemical shift of the lowest energy tautomer is reported. In the two amino acids studied with trifluoromethyl groups, the fluorine chemical shifts are reported as the average of the three fluorine chemical shifts.…”
Section: Methodsmentioning
confidence: 99%
“…For histidine, the different tautomeric states (τ and π) of 2-fluoro and 4-fluoro histidines and analogues were considered. 195051 The fluorine chemical shift of the lowest energy tautomer is reported. In the two amino acids studied with trifluoromethyl groups, the fluorine chemical shifts are reported as the average of the three fluorine chemical shifts.…”
Section: Methodsmentioning
confidence: 99%
“…The π-tautomer of 4-fluorohistidine exhibits a broader spread in carbon chemical shifts than the τ-tautomer. We have recently published the experimental 13 C spectrum of aqueous 4-fluorohistidine, and calculated values of the π-tautomer are in good agreement 60 . The C5 carbon has a relatively shielded nucleus at 101 ppm, and C4 (attached to fluorine) is the most deshielded at 152 ppm.…”
Section: Resultsmentioning
confidence: 68%
“…This preference for the π-tautomer helps explain why 4-fluorohistidine could be successfully incorporated into the RNase A protein in work by Wells and co-workers 29 . Of the two active site histidines, His12 is indicated to be 100% π-tautomer 37 , while the tautomeric form of His119 during proton transfer is unknown (see our recent letter for further discussion) 60 . Having a viable enzyme with 4-FHis substitution may indicate the π-tautomer is the active form during mechanistic steps.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Although solution state tautomeric form has not been definitively established, experimental and theoretical studies suggest His12 of RNase A is in the p-tautomer prior to accepting a proton (and protonated afterward, as seen in this structure). 13,32 Hydrogen bonds help stabilize changes in charge.…”
Section: X-ray and Neutron Diffraction Datamentioning
confidence: 99%
“…4) help to elucidate the hydrogen bonding capacity of the different tautomeric states of histidine; specifically, this study seeks to examine whether or not the tautomeric form of the imidazole species impacts its hydrogen bonding potential at the Ce-H and Cd-H sites. Experimental 13 C NMR evidence found that the tautomeric ratio (t : p) for the imidazole ring in basic solution at 32 AE 3 1C is approximately 4 : 1, 15 and so it would seem quite relevant to seek to investigate the hydrogen bonding potential of each tautomeric state.…”
Section: Introductionmentioning
confidence: 99%